Effect of labile inorganic phosphate status and organic carbon additions on the microbial uptake of phosphorus in soils - Chauhan, B. S., author; Stewart, J. W. B., author; Paul, E. A., author; NRC Research Press, publisher (Colorado State University. Libraries, 1981)
The effect of labile inorganic phosphate (Pi) status of the soil on the decomposition of added cellulose and on the immobilization, mineralization, and redistribution of native and added P in soils was studied in a greenhouse incubation experiment. Cellulose was added at 765 μg C∙g−1 soil with and without P (9 μg∙g−1 soil) every 30 days under adequate N, H2O, and constant temperature to two soils of different available P status. Lack of P eventually slowed down decomposition of added C, but this effect was partially compensated for by increased mineralization of organic P (Po) forms. Added P was redistributed to both P, (58–69%) and Po (42–31%) forms; higher amounts of Po were found in the soil with the highest Pi status. The correlation between microbial P uptake and solution P values was significant, and microbial C:P ratios ranged from 12:1 under high available P conditions to 45:1 where P was in low supply.
Abstract in English and French.
Keywords: soil; organic C; soil biomass; microbial P; lysing; P cycle